KAPABILITAS PEMERINTAH KOTA BATAM DALAM PENGELOLAAN WEBSITE TAHUN 2021-2022 - Siagian, David Vito; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
A government website is an official website managed by a government agency or institution to provide information and public services online. A government website is one manifestation of an electronic-based government system that is currently a program implemented by all regions in Indonesia. This research is located in Batam City, which in 2021-2022 became the city with the second lowest fulfillment of public service standards in the Riau Islands Province and had an electronic-based government system planning index that decreased in 2022 compared to 2021. The purpose of this study is to describe the capabilities of the Batam City Government in managing the website in 2021-2022. The method in this study uses a qualitative approach and a qualitative descriptive research type. The theory used is the capability theory of e-government Capability Theory according to the Harvard JFK School of Government with 3 indicators 1) Support 2) Capacity 3) Value. The results of this study are based on the theory of the Harvard JFK School of Government on the support indicator indicating that objectives have been determined, funds, technology, human resources have been allocated, and the institution of website management has been formed, on the capacity indicator the fulfillment of finances in management is adequate, the availability of technology is still inadequate and the number and skills of human resources are still lacking, for the value indicator seen from the community satisfaction index it is quite good, but the website is still at the stage of inconsistent transactions. The conclusion of this study is that the capability of the Batam City Government is not optimal on the capacity and value indicators, suggestions for the Batam City Government to improve website development to the horizontal integration stage, by improving the fulfillment of technological infrastructure and the fulfillment of the number and skills of human resources needed. Keywords: Local Government, Management, Website.